Analisis Laporan Laba Rugi Pt.Pos Indonesia (Persero) Analysis Income Statement Pt.Pos Indonesia (Persero) - Angeli Besan; Florence Lisa Hattu; Veninsia Uktolseya; Novry Makmara; Nurhani Salampessy (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This research was conducted at PT. Pos Indonesia (Persero) which is engaged in postal services. The purpose of this study is to determine the financial performance of each income at PT. Pos Indonesia (Persero) by using the financial ratios Return On Investment (ROI), Net Profit Margin (NPM) in 2020 to 2021 and financial performance at PT. Pos Indonesia. This study uses a qualitative descriptive research method. The results of this study indicate that the condition of the development of PT. Pos Indonesia (Persero) from 2020 to 2021 can be said to be good. This was influenced by the percentage of net profit or NPM which experienced a positive increase and was followed by an increased ROI value.